2013
DOI: 10.1536/ihj.54.133
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Fms-like Tyrosine Kinase 1 Is a Novel Predictor of Brain Natriuretic Peptide Elevation

Abstract: SummarySoluble fms-like tyrosine kinase 1 (sFlt-1) is an endogenous inhibitor of vascular endothelial growth factor, which is involved in cardiovascular remodeling and atherosclerosis development. To examine the predictive role of sFlt-1 levels in patients with asymptomatic heart failure, we measured circulating sFlt-1 in patients with or without coronary artery disease (CAD). We analyzed 88 Japanese patients with CAD or patients at high risk for atherosclerosis and who were undergoing total risk management fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Thus, PlGF was significantly correlated to inflammatory markers such as hs-CRP and to natriuretic peptide and more precisely BNP [26]. A relationship between PlGF and natriuretic peptides was expected, as PlGF is required for endothelial cell and fibroblast's response to pressure overload [8,9]. Our study extends the relation between sFlt-1 and natriuretic peptides by showing a significant relation with NT-proBNP.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Thus, PlGF was significantly correlated to inflammatory markers such as hs-CRP and to natriuretic peptide and more precisely BNP [26]. A relationship between PlGF and natriuretic peptides was expected, as PlGF is required for endothelial cell and fibroblast's response to pressure overload [8,9]. Our study extends the relation between sFlt-1 and natriuretic peptides by showing a significant relation with NT-proBNP.…”
Section: Discussionsupporting
confidence: 71%
“…It was also recently reported that circulating levels of sFlt-1 and PlGF are elevated in patients with advanced coronary atherosclerosis and HF [13,14]. A paracrine role of sFlt-1 and PlGF as regulators of cardiac adaptation and hypertrophy was also suggested [8,9]. Due to their involvement in the pathogenesis of HF, sFlt-1 and PlGF might represent risk biomarkers for adverse incident CV events in this population.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Recently, two large meta-analyses, by McDonald et al 18 and Bellamy et al 19 , showed that women with PE have higher risks of coronary heart disease and stroke later in life. The serum concentration of sFlt-1 has been shown to be increased in individuals with acute myocardial infarction compared with those without, and it is a good predictor of development of heart failure in patients with coronary heart disease [14][15][16] . Further, in an earlier study, we showed that women with PE had thicker intima and thinner media dimensions and a higher I/M ratio compared with women with normal pregnancy, both during pregnancy and at 1 year postpartum 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Goetze et al 22 found a significantly positive correlation between VEGF and BNP mRNA in an animal study. Kameda et al 23 suggested that high sVEGFR-1 levels may be an effective biomarker to predict the progression of heart failure in patients with CAD. We speculate that an increasing level of sVEGFR-1 by an increasing level of NT-proBNP may be a physiological response to heart failure, designed to decrease angiogenesis in HFrEF and HFmrEF patients, unlike the previous literature.…”
Section: Discussionmentioning
confidence: 99%